The PIV Measurements of Time-Averaged Parameters of the Synthetic Jet for Different Orifice Shapes - Emil Smyk; Paweł Gil; Petra Dančová; Miroslav Jopek (Applied Sciences, 2022)
In the present study, the flow fields generated by a synthetic jet (SJ) were investigated with particle image velocimetry (PIV). The SJ time-averaged parameters, such as velocity, turbulent kinetic energy (TKE), and vorticity, were compared by using the Reynolds number (<semantics>Re=5000</semantics>) and dimensionless stroke length (<semantics>L0=2;10</semantics>). Three different orifice shapes with the same equivalent diameter were used: circle, square, and slot. The flow fields of the investigated parameters were presented and discussed at a distance from the orifice <semantics>x/d≤10</semantics>, and the difference in radial and axial profiles were compared. The impact of the orifice shape and dimensionless stroke length on the investigated parameters was discussed.